Design and Shape Optimization of a Biodegradable Polymeric Stent for Curved Arteries Using FEM - Baradaran, Yasaman; Baghani, Mostafa; Kazempour, Morteza; Hosseini, Seyed Kianoosh; Karimpour, Morad; Baniassadi, Majid (Frontiers in Mechanical Engineering, 2021)
Stent treatment has revealed safe and efficient outcomes for straight arteries, while it is still challenging for curved coronary arteries. On the one hand, a stent should be flexible enough to take the artery's curvature with the least stress to the artery wall. On the other hand, it has to be strong enough to prevent any artery diameter reduction after the implant. In this work, the Genetic algorithm multi-objective optimization method is exploited to provide a Pareto set and designing a curvature stent. The design has been performed base on the appropriate flexibility and radially strength design, depending on the characteristics of a particular case study. In the optimization procedure, flexibility and radial strength have been evaluated based on ASTM standard mechanical tests. These tests have been parametrically simulated using the finite element method. The strut curvature is formed by Spline curvature; whose middle point coordinates are two of the optimization variables. The other optimization variable is the thickness of the stent. Based on the Pareto set achieved from the optimization, five different stent designs have been proposed. In these designs, the middle part of the stent is stiffer (in the plaque aggregated) and benefits more radial strength rather than flexibility. At the stent's extremes, where more deformation takes place, flexibility is weighted more than radial strength. These five design sets differ in their objective weight ratios. At the end of this research, their implementation in a curved vessel is simulated in ABAQUS/CAE, and Von Mises stress distribution after imposing the stent has been analyzed.